Urea Hydrogen Peroxide Reduces the Numbers of Lactobacilli, Nourishes Yeast, and Leaves No Residues in the Ethanol Fermentation - Narendranath, N. V. (American Society for Microbiology, 2000)
Urea hydrogen peroxide (UHP) at a concentration of 30 to 32 mmol/liter reduced the numbers of five Lactobacillus spp. (Lactobacillus plantarum, L. paracasei, Lactobacillus sp. strain 3, L. rhamnosus, and L. fermentum) from ∼10(7) to ∼10(2) CFU/ml in a 2-h preincubation at 30°C of normal-gravity wheat mash at ∼21 g of dissolved solids per ml containing normal levels of suspended grain particles. Fermentation was completed 36 h after inoculation of Saccharomyces cerevisiae in the presence of UHP, even when wheat mash was deliberately contaminated (infected) with L. paracasei at ∼10(7) CFU/ml. There were no significant differences in the maximum ethanol produced between treatments when urea hydrogen peroxide was used to kill the bacteria and controls (in which no bacteria were added). However, the presence of L. paracasei at ∼10(7) CFU/ml without added agent resulted in a 5.84% reduction in the maximum ethanol produced compared to the control. The bactericidal activity of UHP is greatly affected by the presence of particulate matter. In fact, only 2 mmol of urea hydrogen peroxide per liter was required for disinfection when mashes had little or no particulate matter present. No significant differences were observed in the decomposition of hydrogen peroxide in normal-gravity wheat mash at 30°C whether the bactericidal agent was added as H(2)O(2) or as urea hydrogen peroxide. NADH peroxidase activity (involved in degrading H(2)O(2)) increased significantly (P = 0.05) in the presence of 0.75 mM hydrogen peroxide (sublethal level) in all five strains of lactobacilli tested but did not persist in cells regrown in the absence of H(2)O(2). H(2)O(2)-resistant mutants were not expected or found when lethal levels of H(2)O(2) or UHP were used. Contaminating lactobacilli can be effectively managed by UHP, a compound which when used at ca. 30 mmol/liter happens to provide near-optimum levels of assimilable nitrogen and oxygen that aid in vigorous fermentation performance by yeast.